Implementation of guided inquiry learning model to improve student scientific literacy on factors affecting rate of reaction materials - Era Melania; Bertha Yonata (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The research aimed to describe the guided inquiry learning model's effectiveness in improving students' scientific literacy ability. The effectiveness is assessed based on: 1) the implementation of the guided inquiry learning model and 2) students' chemistry learning outcomes on factors affecting the rate of reaction material after implementing the guided inquiry learning model. This research is quantitative descriptive research. It was conducted in an experimental class. The research design used is one group pretest-posttest design. In this research, there were 23 students of class XI MIA 3 SMA Muhammadiyah 10 GKB Gresik in the academic year of 2021/2022 as respondents. For the data collecting, this research uses an observation sheet on implementing a guided inquiry learning model and test sheets for students' scientific literacy on the factors that affect reaction rates material. The data model of implementation percentage that appears at meetings 1 to 3 from the preliminary to the closing activities is 100% (very good). The pretest result shows that 20 students have not achieved the minimum completeness criteria based on three scientific competencies: 1) explaining phenomena scientifically, 2) evaluating and designing scientific experiments, and 3) interpreting data and evidence scientifically. The posttest results show that students' scientific literacy is increased after implementing guided inquiry in the learning process and is 100% classically completed. The Wilcoxon test result shows that the average pretest score and posttest scores in students' scientific literacy ability are significantly different in the realm of knowledge and skills with the value of Asymp. Sig. (2-tailed) = 0.000.